(untitled) - Sternberg, Robert J. (Cambridge, U.K., 2003)
The topics of this revised and updated definitive guide to scientific writing for students and researchers include misconceptions about psychology papers; steps in writing library research papers; steps in writing experimental research papers; rules for writing psychology papers; commonly misused words; Internet resources; and American Psychological Association guidelines for psychology papers. Additional topics include guidelines for data presentation; references for psychology papers; standards for evaluating psychology papers; submitting papers to journals; how to win acceptances of papers by psychology journals; finding book publishers; writing lectures; and writing articles.
Keywords: Report writing,Báo cáo bằng văn bản